2023
DOI: 10.1021/acs.jpcb.2c07012
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Nanoparticle’s Surface Electrostatic Potential in Solution Using Acid–Base Molecular Probes I: In Silico Implementation for Surfactant Micelles

Abstract: Surface electrostatic potential Ψ is a key characteristic of colloid particles. Since the surface of the particles adsorbs various compounds and facilitates chemical reactions between them, Ψ largely affects the properties of adsorbed reactants and governs the flow of chemical reactions occurring between them. One of the most popular methods for estimating Ψ in hydrophilic colloids, such as micellar surfactant solutions and related systems, is the application of molecular probes, predominantly acid−base indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…In total, seventeen molecular probes were examined mainly in SDS and CTAB micellar solutions. The results of our research group have been reported in seventeen articles from 2016 to the present [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. We thought it is expedient to summarize the data obtained and the regularities found.…”
Section: Introductionmentioning
confidence: 80%
“…In total, seventeen molecular probes were examined mainly in SDS and CTAB micellar solutions. The results of our research group have been reported in seventeen articles from 2016 to the present [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. We thought it is expedient to summarize the data obtained and the regularities found.…”
Section: Introductionmentioning
confidence: 80%
“…In Table , they are shown together with several metrics of the indicator’s hydration: the molar fractions of water χ(water) in the local environment of either the whole molecule (except hydrocarbon tails) or the O atom(s) of its ionizing OH or COOH group(s) of acidic and basic forms. The p K a shifts were calculated via eq (the protocol for finding χ(water) is described in the Supporting Information): normalΔ normalp K normala calc app = normalΔ G deprot ( m ) normalΔ G deprot ( w ) R T .25em ln nobreak0em.25em⁡ 10 . Here, Δ G deprot(m) and Δ G deprot(w) are the free energies of deprotonation of the indicator in TX-100 micelles and in water, respectively, which were taken from preceding studies. , …”
Section: Resultsmentioning
confidence: 99%
“…Correspondence between the Ψ values found with the indicator method in vitro and in silico (adapted from Paper I, copyright 2022 American Chemical Society). Black squares: DDP, green diamonds: HHC, red circles: DF (filled for neutral, hollow for cationic), and brown triangles: DODR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations